Knowledge and Skills of Hands-only Cardiopulmonary Resuscitation Training among Secondary School Students: An Interventional Study - Magadi, Khadeja H; Alharbi, Manal F; Soliman, Aziza T; Alashmawy, Maha A (Journal of Education, Health and Sport, 2018)
Objectives: This study aimed to evaluate the effect of a Cardiopulmonary Resuscitation (CPR)Training program (hands only) on retention of knowledge and skills among secondary school female students in Riyadh city. Methodology: An intervention study was conducted. The sample was recruited by multistage sampling to elaborate the targeted schools for research implementation. The allocated school was in Riyadh city, with 92 Female Secondary School. The capacity of this school was 508 students, and 117 students who met the inclusion criteria were included in the study. Data were collected using a structured questionnaire and checklist skills evaluation sheet. Results: In light of the current study findings, the majority of the students were between 17 and 19 years. The present study showed that almost 100% of students were willing to learn CPR; 81.2% and 76.9% of students felt comfortable and confident to perform CPR when needed directly after training and a 4-month follow up, respectively. All students reported that they benefitted from the program. In general, it was found that BLS knowledge was very poor before training while students’ retention of the knowledge and skills ranged from fair to poor after 4-month follow up. Conclusion: Although the current study has only examined female students in secondary schools which limit the generalizability of the result, it provides additional evidence with respect to the Ministry of Education and health care service sector to collaborate and introduce the basic life support program into the school curriculum. National programs are needed by well-equipped nurses for teachers and students in schools regarding basic life support and emergency first aid through the Saudi Ministry of Health in cooperation with nongovernmental societies.